Studi Komputasi Sifat Elektronik dan Sifat Optik Fotoelektroda Titanium Dioksida (TiO2) pada Fasa Anatase dan Rutile - Elvan Yuniarti (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2019)
This research focuses on photoelectric Titanium Dioxide (TiO2) as a tool for Sensitive Solar Cell Dyes (DSSC). Anatase and rutile phase. some of the things studied were: crystal structure, band structure, structural structure, photoelectric optical properties of TiO2. The method used in this study is a calculation using the DFT theory and quantum expresso software. The TiO2 cell unit has the optimal shape for the pure antase TiO2 model which has a parameter a = b 3.785 units, c = 9.514 units, α = β = γ = 90O. The average T-O bond length is 1,966 barrels. This phase has a triclinic lattice type with group space P1 (1) which has a volume unit of 136.2991 A3. The Rutile phase has a parameter a = b = 4.5593 with c = 2,958 stars with α = β = γ = 90O. The average T-O bond length is 2.77 barrels. This phase has a Triclinic lattice type with a space group P1 (1) with a volume unit of 52.44233 A3. The anatase phase of TiO2 has indirect characteristics, namely M and Г. coordinate. Based on the calculation of the large bandgap obtained at 3.2 eV. This is in accordance with the data experiment. The energy of the band tape must be greater than the minimum energy needed for the redox reaction in the dye. While the characteristics of the ribbon emphasize the value of the absorption coefficient in light and the rate of electron recombination. Materials with direct band gab have high combination coefficients but with high combination levels. This greatly influences the DSSC efficiency value. TIO2 Rutile phase has a direct property of 3.5 eV for potential Hubbard energy U + 7. This value is closed to the experiment result.